An update on medical management on Crohn's disease. (January 2015) - Affronti, Andrea; Orlando, Ambrogio; Cottone, Mario
<x xml:space="preserve">Abstract</x> Introduction: The management of Crohn's disease (CD) is continuously evolving. New issues emerging from more recent studies could influence the decision-making process in clinical practice. Areas covered: The aim of this review article is to highlight critical issues on the management of CD, new evidence from clinical trials, long-term prospective studies and real life experience, beyond the current guidelines. Expert opinion: The role of mucosal healing in clinical practice is uncertain, clinical remission remains the primary end point. The timing for the definition of steroid-resistant CD should be considered between 2 and 4 weeks. Early treatment strategy with immunomodulators is effective for inducing remission but no controlled data are available regarding long-term outcome. Combination therapy (anti-TNFs agents and immunosuppressors) is more effective than single therapy but there is a lack of long-term data and an increased risk of malignancy. The effect of mesalazine, metronidazole and azathioprine in reducing postoperative recurrence is not clinically relevant; biologics are effective, but the duration of treatment is unknown. New drugs are under investigation in order to find exit strategy for patients who no longer respond to biologics. Combination therapy set on anti-TNF-α is until now the best option both to achieve fistula healing and avoid recurrence